PETA JALAN PENDIDIKAN REKAYASA ENERGI BAGI INDONESIA -- SEBUAH PROPOSAL - Leonard Lisapaly; Togar Harapan Pangaribuan; Atmonobudi Soebagio (Lektrokom : Jurnal Ilmiah Teknik Elektro, 2019)
Indonesia has ratified 17 Sustainable Development Goals (SDG) recommended by the United Nations to all countries. The development itself cannot be carried out without the availability of electricity and fuel. Unfortunately, most of the electricity and transportation depend on fossil fuels, which will run out in the next 30 years. Besides its diminishing reserves, fossil fuels are the largest contributor to CO2 emissions in the world. To develop electricity from renewable energy, Indonesia needs to prepare its experts and operators through mid and high education to carry out research, operations and future development. This paper offers a road map for higher education and its direction of research and development in the field of renewable energy engineering.